Acts 8: 4-25: The Amazing Magic versus The Joyful Gospel - Chandra Han (Jurnal Jaffray, 2021)
Magic as one significant theme in the Acts of the Apostles is not yet significantly exposed. In the Greco-Roman era, magic had become a part of people’s lives from the lowest to the highest status, such as the Roman Emperor. The confrontation between magic which is likely amazing, with the joyful gospel is essential to be examined. The gospel's victory over magic is prominent for Christians and Church ministry because the power of the gospel that overcomes magic is the anchor of Christianity. This article will employ the literature research method within the qualitative research category. The most extended episode of the magical passage, Acts 8: 4-25, will be examined to figure out the distinctive feature between magic and the gospel and how the gospel overcome magic and the gospel is then widely spread throughout the region of Samaria and even to the end of the world. The literal translation and the text variant will be the first part of the examination. The following study is to demonstrate the structure. The next part is the exegesis to figure out the meaning of the text within the relevant context, including the distinction between magic and Christianity. The last part is the Implications within the contemporary era for Christians and Church ministry and conclusion.